Analyze the Efficiency of Activities Using Activity Based Management (Case Study at PT. IMA Montaz) - Muammar Khaddafi; Dyan Anggrea Ningrum; Servo Sari; Asnah Putri; Mustika Shahana; Khaira Khirnika (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
Increasingly sharp global competition causes the characteristics of the business environment faced by management to be dynamic and change rapidly. To maintain its survival, a company must be able to achieve its goal, namely obtaining maximum profits. The costs incurred by the company must really be costs that add value to the product so that there will be no wasted costs. Therefore, cost efficiency has an important meaning for companies in maintaining their presence in the business world. One way that companies can use to achieve cost efficiency is through activity-based management or Activity Based Management (ABM). The purpose of this research is to find out how Activity Based Management is implemented in water management and to find out whether the Activity Based Management carried out is able to encourage efficiency. production cost.